A BOPP composite film and preparation method thereof

By adopting a three-layer structure BOPP composite film design, combined with the design of polypropylene-based film, strengthening the inner membrane and scratch-resistant surface film, the problem of poor wear resistance of existing BOPP films is solved, significantly improving scratch-resistant and mechanical properties, and extending service life.

CN119427874BActive Publication Date: 2025-04-25TIANJIN HUAHENG PACKAGING MATERIALS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510018516.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-25
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The surface of the existing BOPP film has poor wear resistance and is easily scratched during post-processing, transportation and use, affecting its service life.

Method used

The BOPP composite film design adopts a three-layer structure, including a polypropylene-based film, a reinforced inner membrane and a scratch-resistant surface film. The reinforced inner membrane is made of polypropylene and modified silicon carbide frame reinforcement fluid, and the scratch-resistant surface membrane is made of polypropylene and scratch-resistant modifier. The composite film was prepared by blending extrusion and bidirectional stretching processes.

Benefits of technology

It significantly improves the scratch resistance and mechanical properties of the BOPP composite membrane, extends the service life, and improves the overall mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a BOPP composite film and a preparation method thereof, wherein the BOPP composite film comprises a polypropylene base film, a reinforced inner film and an anti-scratch surface film, wherein the reinforced inner film is located above the polypropylene base film, and the anti-scratch surface film is located above the reinforced inner film; the reinforced inner film is made of the following raw materials in parts by weight: 80-98 parts of polypropylene and 2-20 parts of a reinforcing agent; and the anti-scratch surface film is made of the following raw materials in parts by weight: 90-99 parts of polypropylene and 1-10 parts of an anti-scratch modifier. The BOPP composite film of the present invention arranges the reinforced inner film and the anti-scratch surface film on the polypropylene base film, thereby improving the overall anti-scratch performance of the BOPP composite film, extending the service life of the BOPP composite film, and further improving the mechanical properties of the overall BOPP composite film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical materials, and in particular relates to a BOPP composite film and a preparation method thereof. Background Art

[0002] Biaxially oriented polypropylene (BOPP) film has the advantages of high strength, high transparency, high gloss, high stiffness, good thermal stability and non-toxicity. It is of high quality and moderate price. It is widely used in packaging of food, beverage, cigarette, clothing and other industries, and has rapidly occupied the plastic packaging market.

[0003] Most existing BOPP films have poor surface wear resistance and are often scratched by contact with hard objects during post-processing, transportation and use, thus affecting their service life. Summary of the invention

[0004] In view of this, the present invention aims to overcome the defects in the prior art and proposes a BOPP composite film and a preparation method thereof.

[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] A BOPP composite film, comprising a polypropylene base film, a reinforced inner film and an anti-scratch surface film, wherein the reinforced inner film is located above the polypropylene base film, and the anti-scratch surface film is located above the reinforced inner film; the reinforced inner film is made of the following raw materials in parts by weight: 80-98 parts of polypropylene and 2-20 parts of a reinforcing agent; the anti-scratch surface film is made of the following raw materials in parts by weight: 90-99 parts of polypropylene and 1-10 parts of an anti-scratch modifier.

[0007] Preferably, the reinforced inner membrane is made of raw materials including the following parts by weight: 92-98 parts of polypropylene and 2-8 parts of a reinforcing agent.

[0008] Furthermore, the reinforcing agent comprises a modified silicon carbide skeleton and a reinforcing liquid in a mass ratio of 1:80-150.

[0009] Furthermore, the preparation method of the reinforcing liquid comprises the following steps: stirring the epoxy acrylate resin, the curing agent and the initiator once, then adding the modified metal oxide powder thereto, stirring for a second time, and mixing them evenly to obtain the reinforcing liquid.

[0010] Furthermore, the mass ratio of the epoxy acrylate resin, curing agent, initiator and modified metal oxide powder is 50-100: 1-20: 0.1-5: 1-20; the time of the first stirring step is 1-3 hours; the time of the second stirring step is 0.1-3 hours.

[0011] Furthermore, the preparation method of the modified metal oxide powder comprises the following steps: adding the metal oxide powder to a solvent, then adding a coupling agent thereto, stirring under heating conditions, filtering after the reaction is completed, and obtaining the modified metal oxide powder; the metal oxide is at least one of aluminum oxide or titanium dioxide; the coupling agent is 3-(methacryloyloxy)propyltrimethoxysilane or ethyltriethoxysilane; the temperature of the stirring step is 20-50°C, and the time is 1-5 hours.

[0012] The modified metal oxide powder improves the strength and toughness of the reinforced inner film. After being mixed with the modified silicon carbide skeleton, the monomers in the reinforcing liquid are adsorbed on the modified silicon carbide skeleton, thereby improving the overall strength of the reinforcing agent.

[0013] Furthermore, the preparation method of the modified silicon carbide skeleton comprises the following steps: acidifying silicon carbide, then adding it to a solvent, adding a coupling agent thereto, stirring and washing to obtain a silicon nitride intermediate, adding the silicon nitride intermediate to a dimethylacetamide solvent containing vinyl acetate, adding a photoinitiator thereto, and obtaining the modified silicon carbide skeleton after ultraviolet light irradiation, washing, and drying.

[0014] The vinyl acetate is grafted onto the surface of silicon carbide through reaction, so that the modified silicon carbide skeleton is evenly dispersed in polypropylene and forms a network structure with polypropylene, thereby improving the mechanical strength and wear resistance of the reinforced inner film and also improving the dispersion performance of the reinforcing liquid in polypropylene.

[0015] Furthermore, the lower surface of the anti-scratch surface film is roughened; the roughening method is magnetron sputtering.

[0016] Furthermore, the anti-scratch modifier is bisphenol A epoxy resin and Bayhydur XP2655 in a mass ratio of 1:0.5-2. The hydroxyl group of bisphenol A epoxy resin reacts with the isocyanate group of Bayhydur XP2655 to form a compact structure, further improving the adhesion of the anti-scratch surface film.

[0017] The method for preparing the BOPP composite film comprises the following steps:

[0018] Step 1 is to extrude polypropylene to obtain a polypropylene base film;

[0019] Step 2 is to blend and extrude the polypropylene and the reinforcing agent to obtain a reinforced inner film;

[0020] Step 3 is to blend and extrude the polypropylene and the anti-scratch modifier to obtain an anti-scratch surface film;

[0021] Step 4 is to send the reinforced inner film into the main extruder for melting, put the anti-scratch surface film and the polypropylene base film into two auxiliary extruders for melting, extrude through a three-layer structure die, and perform biaxial stretching to obtain the BOPP composite film.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] The BOPP composite film described in the present invention arranges a reinforced inner film and a scratch-resistant surface film on a polypropylene base film, thereby improving the overall scratch resistance of the BOPP composite film; wherein, an anti-scratch modifier is introduced into the scratch-resistant surface film, thereby improving the overall mechanical properties and scratch resistance of the scratch-resistant surface film, and a reinforcing agent containing a modified silicon carbide skeleton and a reinforcing liquid is added to the reinforced inner film, thereby improving the bonding effect between the reinforced inner film and the scratch-resistant surface film, thereby greatly improving the scratch resistance of the combination of the reinforced inner film and the scratch-resistant surface film, extending the service life of the BOPP composite film, and further improving the overall mechanical properties of the BOPP composite film. DETAILED DESCRIPTION

[0024] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0025] The strengthening liquid in the embodiments and comparative examples of the present invention is prepared by a method comprising the following steps:

[0026] (1) 30 g of aluminum oxide powder was added to 100 mL of isopropanol and dispersed for 2 hours, and then 0.5 g of 3-(methacryloyloxy)propyltrimethoxysilane was added thereto, and stirred at 45° C. for 3 hours. After the reaction was completed, the mixture was filtered to obtain the modified aluminum oxide powder;

[0027] (2) 80 g of epoxy acrylate resin, 2 g of neopentyl glycol diacrylate and 1 g of thioxanthone were stirred for 2 hours, and then 10 g of modified alumina powder was added thereto, and stirred for a second time for 1 hour. After mixing evenly, the reinforcing liquid was obtained.

[0028] The modified silicon carbide skeleton in the embodiments and comparative examples of the present invention is prepared by a method comprising the following steps:

[0029] (1) 50 g of silicon carbide was treated with nitric acid at 120° C. for 2 hours, then added to an ethanol solution, to which 2 g of γ-mercaptopropyltrimethoxysilane was added, and after stirring and washing, a silicon nitride intermediate was obtained;

[0030] (2) The silicon nitride intermediate is added to a dimethylacetamide solvent containing 30% vinyl acetate, 1 g of a photoinitiator is added thereto, and after ultraviolet light irradiation, washing, and drying, the modified silicon carbide skeleton is obtained.

[0031] The present invention will be described in detail below with reference to the embodiments.

[0032] Example 1

[0033] A method for preparing a BOPP composite film comprises the following steps:

[0034] (1) 10 g of modified silicon carbide skeleton was mixed with 90 g of reinforcing liquid, and stirred for 1 hour to obtain a reinforcing agent. Polypropylene with a mass ratio of 96:4 was co-extruded to obtain a reinforced inner membrane;

[0035] (2) Mixing bisphenol A epoxy resin and Bayhydur XP2655 in a mass ratio of 1:1 to obtain an anti-scratch modifier, and blending and extruding polypropylene and the anti-scratch modifier in a mass ratio of 98:2 to obtain an anti-scratch surface film;

[0036] (3) The reinforced inner film is fed into a main extruder for melting, and the anti-scratch surface film and the polypropylene base film are fed into two auxiliary extruders for melting, extruded through a three-layer structure die head, and biaxially stretched to obtain the BOPP composite film.

[0037] Example 2

[0038] A method for preparing a BOPP composite film comprises the following steps:

[0039] (1) 10 g of modified silicon carbide skeleton was mixed with 120 g of reinforcing liquid, and stirred for 1 hour to obtain a reinforcing agent. Polypropylene with a mass ratio of 96:4 was co-extruded to obtain a reinforced inner membrane;

[0040] (2) Mixing bisphenol A epoxy resin and Bayhydur XP2655 in a mass ratio of 1:1 to obtain an anti-scratch modifier, and blending and extruding polypropylene and the anti-scratch modifier in a mass ratio of 98:2 to obtain an anti-scratch surface film;

[0041] (3) The reinforced inner film is fed into a main extruder for melting, and the anti-scratch surface film and the polypropylene base film are fed into two auxiliary extruders for melting, extruded through a three-layer structure die head, and biaxially stretched to obtain the BOPP composite film.

[0042] Example 3

[0043] A method for preparing a BOPP composite film comprises the following steps:

[0044] (1) 10 g of modified silicon carbide skeleton was mixed with 90 g of reinforcing liquid, and stirred for 1 hour to obtain a reinforcing agent. Polypropylene with a mass ratio of 94:6 was co-extruded to obtain a reinforced inner membrane;

[0045] (2) Mixing bisphenol A epoxy resin and Bayhydur XP2655 in a mass ratio of 1:1 to obtain an anti-scratch modifier, and blending and extruding polypropylene and the anti-scratch modifier in a mass ratio of 98:2 to obtain an anti-scratch surface film;

[0046] (3) The reinforced inner film is fed into a main extruder for melting, and the anti-scratch surface film and the polypropylene base film are fed into two auxiliary extruders for melting, extruded through a three-layer structure die head, and biaxially stretched to obtain the BOPP composite film.

[0047] Comparative Example 1

[0048] A method for preparing a BOPP composite film comprises the following steps:

[0049] (1) 10 g of modified silicon carbide skeleton was mixed with 90 g of epoxy acrylate resin, and stirred for 1 hour to obtain a reinforcing agent. Polypropylene with a mass ratio of 96:4 was co-extruded to obtain a reinforced inner film;

[0050] (2) Mixing bisphenol A epoxy resin and Bayhydur XP2655 in a mass ratio of 1:1 to obtain an anti-scratch modifier, and blending and extruding polypropylene and the anti-scratch modifier in a mass ratio of 98:2 to obtain an anti-scratch surface film;

[0051] (3) The reinforced inner film is fed into a main extruder for melting, and the anti-scratch surface film and the polypropylene base film are fed into two auxiliary extruders for melting, extruded through a three-layer structure die head, and biaxially stretched to obtain the BOPP composite film.

[0052] Comparative Example 2

[0053] A method for preparing a BOPP composite film comprises the following steps:

[0054] (1) 10 g of silicon carbide was mixed with 90 g of reinforcing liquid and stirred for 1 hour to obtain a reinforcing agent. Polypropylene with a mass ratio of 96:4 was co-extruded to obtain a reinforced inner film;

[0055] (2) Mixing bisphenol A epoxy resin and Bayhydur XP2655 in a mass ratio of 1:1 to obtain an anti-scratch modifier, and blending and extruding polypropylene and the anti-scratch modifier in a mass ratio of 98:2 to obtain an anti-scratch surface film;

[0056] (3) The reinforced inner film is fed into a main extruder for melting, and the anti-scratch surface film and the polypropylene base film are fed into two auxiliary extruders for melting, extruded through a three-layer structure die head, and biaxially stretched to obtain the BOPP composite film.

[0057] Comparative Example 3

[0058] A method for preparing a BOPP composite film comprises the following steps:

[0059] (1) Mixing bisphenol A epoxy resin and Bayhydur XP2655 in a mass ratio of 1:1 to obtain an anti-scratch modifier, and blending and extruding polypropylene and the anti-scratch modifier in a mass ratio of 98:2 to obtain an anti-scratch surface film;

[0060] (2) The inner film is fed into a main extruder for melting, and the anti-scratch surface film and the polypropylene base film are fed into two auxiliary extruders for melting, extruded through a three-layer structure die head, and biaxially stretched to obtain the BOPP composite film.

[0061] Comparative Example 4

[0062] A method for preparing a BOPP composite film comprises the following steps:

[0063] (1) 10 g of modified silicon carbide skeleton was mixed with 90 g of reinforcing liquid, and stirred for 1 hour to obtain a reinforcing agent. Polypropylene with a mass ratio of 96:4 was co-extruded to obtain a reinforced inner membrane;

[0064] (2) The reinforced inner film is fed into a main extruder for melting, and the surface film and the polypropylene base film are fed into two auxiliary extruders for melting, and then extruded through a three-layer structure die head for biaxial stretching to obtain the BOPP composite film.

[0065] The BOPP composite films obtained in Examples 1-3 and the BOPP composite films obtained in Comparative Examples 1-4 were subjected to a peel strength test (GB / T 8808-1988) and an abrasion resistance test (GB / T 3960-2016). The results are shown in Table 1.

[0066] Table 1 Results

[0067]

[0068] As shown in Table 1, the peel strength and wear resistance of the composite films obtained in Examples 1-3 are greatly improved compared with those in Comparative Examples 1-4. Compared with Example 1, Comparative Example 1 replaces the reinforcing liquid with epoxy acrylate resin, which has a certain impact on its scratch resistance and mechanical properties. Comparative Example 2 replaces the modified silicon carbide skeleton with silicon carbide, so that the monomer in the reinforcing liquid cannot adhere to the skeleton, affecting the mechanical strength of the reinforcing inner film itself, and further affecting the resultant effect of the reinforcing inner film and the scratch-resistant surface film, thereby affecting the effect of the overall composite film. No reinforcing agent is added to the inner film of Comparative Example 3, and the mechanical properties and scratch resistance are greatly reduced. No scratch-resistant modifier is added to the surface film of Comparative Example 4, and the performance is quite different from that of Comparative Example 1.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A BOPP composite film, characterized in that: The BOPP composite film comprises a polypropylene base film, a reinforced inner film and an anti-scratch surface film, wherein the reinforced inner film is located above the polypropylene base film, and the anti-scratch surface film is located above the reinforced inner film; the reinforced inner film is made of the following raw materials in parts by weight: 80-98 parts of polypropylene and 2-20 parts of a reinforcing agent; the anti-scratch surface film is made of the following raw materials in parts by weight: 90-99 parts of polypropylene and 1-10 parts of an anti-scratch modifier; The reinforcing agent comprises a modified silicon carbide skeleton and a reinforcing liquid in a mass ratio of 1:80-150; The preparation method of the strengthening liquid comprises the following steps: stirring the epoxy acrylate resin, the curing agent and the initiator once, then adding the modified metal oxide powder thereto, stirring twice, and mixing evenly to obtain the strengthening liquid; The preparation method of the modified metal oxide powder comprises the following steps: adding the metal oxide powder to a solvent, then adding a coupling agent thereto, stirring under heating conditions, filtering after the reaction is completed, and obtaining the modified metal oxide powder; the metal oxide is at least one of aluminum oxide or titanium dioxide; the coupling agent is 3-(methacryloyloxy)propyltrimethoxysilane or ethyltriethoxysilane; the temperature of the stirring step is 20-50° C., and the time is 1-5 hours; The preparation method of the modified silicon carbide skeleton comprises the following steps: acidifying silicon carbide, then adding it to a solvent, adding a coupling agent thereto, stirring and washing to obtain a silicon nitride intermediate, adding the silicon nitride intermediate to a dimethylacetamide solvent containing vinyl acetate, adding a photoinitiator thereto, irradiating with ultraviolet light, washing, and drying to obtain the modified silicon carbide skeleton; The anti-scratch modifier is bisphenol A epoxy resin and Bayhydur XP2655 in a mass ratio of 1:0.5-2.

2. The BOPP composite film according to claim 1, characterized in that: The mass ratio of the epoxy acrylate resin, curing agent, initiator and modified metal oxide powder is 50-100: 1-20: 0.1-5: 1-20; the time of the first stirring step is 1-3 hours; the time of the second stirring step is 0.1-3 hours.

3. The BOPP composite film according to claim 1, characterized in that: The lower surface of the anti-scratch surface film is roughened; the roughening method is magnetron sputtering.

4. The method for preparing the BOPP composite film according to any one of claims 1 to 3, characterized in that: The steps include: Step 1 is to extrude polypropylene to obtain a polypropylene base film; Step 2 is to blend and extrude the polypropylene and the reinforcing agent to obtain a reinforced inner film; Step 3 is to blend and extrude the polypropylene and the anti-scratch modifier to obtain an anti-scratch surface film; Step 4 is to send the reinforced inner film into the main extruder for melting, put the anti-scratch surface film and the polypropylene base film into two auxiliary extruders for melting, extrude through a three-layer structure die, and perform biaxial stretching to obtain the BOPP composite film.

Citation Information

Patent Citations

  • Novel film

    CN220594297U